1972
DOI: 10.1017/s1446788700011241
|View full text |Cite
|
Sign up to set email alerts
|

One-sided ideals in near-rings of transformations

Abstract: Let (G, +) be an arbitrary group and let T0(G) = {f∈ Map(G, G): 0f = 0}; the system composed of T0(G) and the operations of pointwise addition and composition of functions form a (left) near-ring. Berman and Silverman, in their investigation of near-rings of transformations [3], found that for every group G the associated near-ring of transformations T0(G) has no proper ideals. In the present paper left and right ideals of T0(G) are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…near-ring is a normal subgroup closed under right multiplication. So the rest follows from Theorem 2.4 and a description of the right ideals of M 0 (H) obtainable from Heatherly (1972) or Pilz (1977). COROLLARY 3.4.…”
Section: The Right Ideals Of Rmentioning
confidence: 96%
See 1 more Smart Citation
“…near-ring is a normal subgroup closed under right multiplication. So the rest follows from Theorem 2.4 and a description of the right ideals of M 0 (H) obtainable from Heatherly (1972) or Pilz (1977). COROLLARY 3.4.…”
Section: The Right Ideals Of Rmentioning
confidence: 96%
“…Using the results of Heatherly (1972) or Pilz (1977), we can write M 0 {H) as a direct sum of right ideals as follows :…”
Section: (G) = A(g) = E(g) = Rmentioning
confidence: 99%
“…Transformation near-rings 411 PROOF. Heatherly (1972) has shown that if x is a nonzero element of G, then v4({x}) is a maximal right ideal of T 0 (G). Now suppose S is a maximal element of 3b.…”
Section: Lemma 1 Let S Be a Right Ideal Of T 0 (G) Then Cces If Andmentioning
confidence: 99%
“…The purpose of this note is to characterize maximal right ideals of T 0 (G), the (left) mear-ring of transformations from a group (G, + ) into itself which leave zero fixed. Using this characterization, we answer some questions raised by Heatherly (1972).…”
mentioning
confidence: 97%
See 1 more Smart Citation